NURSING CARE QUALITY WITH PATIENT SATISFACTION - Haryanti, Dwi Yunita; Elmaghfuroh, Dian Ratna (Universitas Airlangga, 2025)
Abstract Background The community satisfaction index has decreased compared to the previous year, along with a decline in patient satisfaction. This reflects a growing public dissatisfaction with the services provided. The purpose of this study was to prove the effect of nursing care quality on patient satisfaction. Method This research was analytic observational research with a cross sectional design. The sample was 125 respondents obtained from 4 health clinics which selected by cluster sampling technique. The Perceptions of the Quality Nursing Care Scale to measure quality of nursing care and the Patient Satisfaction with Nursing Care Quality Questionnaire instrument was used to measure patient satisfaction. Data was analyzed with multiple linear regression. Result Based on the results of regression analysis, it can be concluded that the calculated F value is 666.4 and a significance value of 0.000. So it can be concluded that there is an effect of nursing care quality variables on patient satisfaction simultaneously. The coefficient of determination of nursing care quality variables on patient satisfaction is 0.901, which means that the influence of interpersonal care, efficiency, comfort, information, environment and competence variables simultaneously on patient satisfaction variables is 90%, the remaining 10% is influenced by other variables not examined in this study. Conclusion There is an influence of nursing care quality on patient satisfaction. The most dominant variable is nurse competence, where there are indicators of cognitive ability, skills and ability to communicate effectively and assertively. Increasing patient satisfaction will be easily achieved when service quality is maintained and patient safety becomes the main thing that is prioritized.